2012
DOI: 10.1111/j.1471-4159.2011.07604.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cbln1 and Cbln2 functions using transgenic and knockout mice

Abstract: Cbln1 is the prototype of a family of secreted neuronal glycoproteins (Cbln1-4) and its genetic elimination results in synaptic alterations in cerebellum and striatum. In cerebellum, Cbln1 acts as a bi-functional ligand bridging pre-synaptic β-neurexins on granule cells to post-synaptic Grid2 on Purkinje neurons. Although much is known concerning the action of Cbln1, little is known of the function of its other family members. Here we show that Cbln1 and Cbln2 have similar binding activities to β-neurexins and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 37 publications
2
45
0
Order By: Relevance
“…97, 98 This is of particular relevance given the common association of TS with ADHD and OCD and that the GRID1 knockout mouse presents with hyperactivity and aberrant emotional and social behaviours, 98 which contrasts markedly with the ataxic presentation of the GRID2 knockout mouse. 99 The behavioural phenotype of the CBLN2 knockout mouse 100 is eagerly anticipated. At the molecular level GRID1's preferential role with CBLN2 in the induction of inhibitory presynaptic differentiation 101 suggests that reduced inhibitory synaptogenesis may represent a distinguishing molecular feature of TS compared with ASD but this remains to be tested.…”
Section: Synaptic Model Mechanismsmentioning
confidence: 99%
“…97, 98 This is of particular relevance given the common association of TS with ADHD and OCD and that the GRID1 knockout mouse presents with hyperactivity and aberrant emotional and social behaviours, 98 which contrasts markedly with the ataxic presentation of the GRID2 knockout mouse. 99 The behavioural phenotype of the CBLN2 knockout mouse 100 is eagerly anticipated. At the molecular level GRID1's preferential role with CBLN2 in the induction of inhibitory presynaptic differentiation 101 suggests that reduced inhibitory synaptogenesis may represent a distinguishing molecular feature of TS compared with ASD but this remains to be tested.…”
Section: Synaptic Model Mechanismsmentioning
confidence: 99%
“…Cbln1, Cbln2, and Cbln4 KO mice are viable; thus, individual cerebellins are not essential for survival (Hirai et al, 2005; Rong et al, 2012; Wei et al, 2012; Haddick et al, 2014). Only Cbln1 KO mice have been analyzed in detail, and exhibit a phenotype that is virtually identical to that of GluD2 KO mice (Hirai et al, 2005; Otsuka et al, 2016; Kusnoor et al, 2010; Ito-Ishida et al, 2008 and 2014).…”
Section: Cerebellinsmentioning
confidence: 99%
“…In cerebellum – the only brain region extensively analyzed - Cbln1 and GluD2 KO mice exhibit a decrease in parallel-fiber synapses formed by granule cells on Purkinje cell spines, with a loss of presynaptic terminals and the appearance of ‘naked spines’ (Kashiwabuchi et al, 1995; Hirai et al, 2005; Rong et al, 2012). Importantly, the loss of parallel-fiber synapses is only partial (~30–50% depending on the study) and primarily found on distal dendrites of Purkinje cells, and is not associated with a decrease in spine density (hence the ‘naked spines’; Hirai et al, 2005).…”
Section: Cerebellinsmentioning
confidence: 99%
“…12,13 The GluRD2 general structure is similar to other iGluRs, with an extracellular ligand binding domain composed of 2 segments (S1 and S2), 4 transmembrane segments (M1-M4) of which M1, M3, and M4 are responsible for the channel pore formation, and 3 linkers (S1M1, M3S2, S2M4). 15 Recently, it was proven, in vitro and in mice, that GluRD2 and cerebellin-1 form a complex acting as a synapse organizer between PFs and PCs 16,17 and that GluRD2 also has a major role in long-term depression at this synapse, 13,[18][19][20] possibly through the regulation of AMPA receptors endocytosis. 15 Recently, it was proven, in vitro and in mice, that GluRD2 and cerebellin-1 form a complex acting as a synapse organizer between PFs and PCs 16,17 and that GluRD2 also has a major role in long-term depression at this synapse, 13,[18][19][20] possibly through the regulation of AMPA receptors endocytosis.…”
Section: Individualsmentioning
confidence: 99%